ANALISIS KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN LAMPUNG UTARA - Andy Fitriyadi Dharmat Tilaar (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
uncover performance issues. It is attracting writers to research and study further by testing andanalyzing the extent to which "The Influence of Leadership Styles and Motivation Work To PerformanceEmployees Dinas Sosial, Tenaga Kerja dan Transmigrasi Kabupaten Lampung Tengah ". Thehypothesis is: Suspected leadership style and work motivation affect the performance of Social ServiceEmployees Manpower and Dinas Sosial, Tenaga Kerja dan Transmigrasi Kabupaten LampungTengah.This research was conducted using survey method. The entire population is in the EmployeeDinas Sosial, Tenaga Kerja dan Transmigrasi Kabupaten Lampung Tengah regency as many as 55people, in which samples were taken using saturated sample. The reliability of the instrument iscalculated by the formula product moment correlation, while the reliability of the instrument is calculatedby the formula Alpha crobach.Results of research leadership style and work motivation affect the performance of Dinas Sosial,Tenaga Kerja dan Transmigrasi Kabupaten Lampung Tengah with a coefficient of determination of43.3% (percent) of the variation of the effect of changes in leadership style and work motivation mayexplain Employee Performance and Dinas Sosial, Tenaga Kerja dan Transmigrasi Kabupaten LampungTengah. Whereas 56.7% (percent) the rest is the influence of variables or other factors outside themodel.